Pengaruh Brand Ambassador NCT Dream dan Social Media Marketing terhadap Purchase Intention dengan Brand Awareness sebagai Variable Intervening: - Afiaty Caesaria Azizah; Henny Welsa; Lusia Tria Hatmanti Hutami (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
This study aims to find out how much influence NCT DREAM Brand Ambassador and Social Media Marketing have on Purchase Intention with Brand Awareness as an intervening variable (Case Study on Lemonilo Product Consumers in Yogyakarta City). The population in this study was all consumers of Lemonilo products. The sample in this study was 100 respondents using the Nonprobability Sampling technique used is purposive sampling where the researcher selects the sample subjectively with certain considerations. This data was taken using a questionnaire through a google form, after the result questionnaire was collected, data processing and analyzing data was carried out using the IBM SPSS version 22 application. The results of this study show that Brand ambassadors have a positive and significant effect on brand awareness. Social media marketing has a positive and significant effect on brand awareness. Brand awareness has a significant and positive effect on purchase intention. Brand ambassadors have a significant and positive effect on purchase intention. Social media marketing has a positive and significant effect on purchase intention. ]Keywords: Brand Ambassador, Brand Awareness, Social Media Marketing, Purchase Intention